Enhancing Elementary Students’ Critical Thinking and Problem-Solving Skills Through the Implementation of Problem-Based Learning at Muhammadiyah 4 Batu Elementary School - Rohmah, Rissana Aprilia; Budiono, B.; Husamah, H. (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
In the era of rapidly evolving educational paradigms, critical thinking and problem-solving abilities have become essential competencies for 21st-century learners. However, few studies in the Indonesian elementary context have triangulated data from classroom observations, teacher interviews, and questionnaires to provide empirical evidence of how Problem-Based Learning (PBL) enhances these skills. This study examined the association between PBL and students’ behavioral indicators of critical thinking and problem-solving at Muhammadiyah 4 Batu Elementary School. Employing a qualitative descriptive design, the research involved three Grade 5 classes (5A, 5B, 5C; comprising a total of 87 students) and three teachers, spanning six PBL sessions over one semester. Data were collected through classroom observations, teacher and student interviews, and questionnaire surveys to capture the holistic dynamics of PBL in classroom practice. The observation rubric assessed four behavioral indicators—responsibility, confidence, initiative, and discipline—as proxies of critical thinking and problem-solving competence. The results reveal that PBL is associated with higher levels of engagement, curiosity, and analytical reasoning through structured problem scenarios that require collaboration and inquiry. Quantitative findings showed that class 5C achieved the highest responsibility (83.9%), confidence (87.4%), and discipline (86.2%), while class 5A demonstrated the strongest initiative (79.3%). Teachers’ interviews confirmed that consistent application of the five PBL stages—problem orientation, inquiry, design, presentation, and reflection—coincided with stronger behavioral outcomes. These findings suggest that PBL supports metacognition, self-regulation, and reflective learning aligned with Indonesia’s Kurikulum Merdeka. The study contributes new evidence on elementary-level PBL implementation by integrating validated behavioral rubrics, teacher perspectives, and classroom artifacts within a single descriptive framework.